Structural analysis of combination of plastic materials in relation to fibre-metal laminates - Wong, Kai Wen (Nanyang Technological University, 2021)
In this project, the structural properties of the combination of plastic material in relation to Fiber-Metal Laminates is investigated. A combination of Acrylic and Polycarbonate is used for this project. To simulate a stacking sequence similar to that of a Fiber-Metal laminate, a stacking sequence of Acrylic-Polycarbonate- Acrylic (APA) and Polycarbonate-Acrylic-Polycarbonate (PAP) is proposed here. The tensile properties of the proposed plastic combination were then tested using the Instron Universal testing machine. Mainly, the Young’s modulus, maximum stress and strain, maximum force and deflection were obtained from the test. Different lengths of 100mm, 150mm, and 200mm of the plastic combination were also tested and examined. The modes of failure of the plastic combination were recorded during the testing phase. The tensile test results are then compiled and compared with the single- layer Polycarbonate and Acrylic and also the plastic combination itself. Both plastic combinations show little to no signs of deformation and they behave similar to the dominant material in the plastic combination. APA behaves more like Acrylic whereas PAP behaves more like Polycarbonate in terms of their structural properties.